The Development of Distribution Channels of Processed Agricultural Products from Local Wisdom of Khlong Khuean Sub-district Chachoengsao Province to Efficiency Retail Business - Kitiyajonsakun, Oranuch; Matman*, Phawinee; Tahtsanaphong, Thatsanawan (Journal of Management Science, Ubon Ratchathani University, 2022)
The objectives of this research were (1) to study consumers’ processed agricultural products purchasing behavior. (2) to study the situation of distribution channels in the retail business of processed agricultural products (3) to study the strengths, weaknesses, opportunities and threats in the distribution channels of processed agricultural products from local wisdom of Khlong Khuean subdistrict Chachoengsao province (4) to set guidelines for distribution channels of processed agricultural products from local wisdom of Khlong Khuean subdistrict. It is a quantitative research for the first objective by using a questionnaire to collect data from 400 people and qualitative research for the second, third and fourth objectives by collecting data from producers of processed agricultural products in Khlong Khuean subdistrict, 35 people and from 10 representatives of retail stores. The tool used for data collection was in-depth interview. The results of the study were consumers buy processed agricultural products from souvenir shops. The strength of processed agricultural products was outstanding in taste its weakness was distribution of products to retail stores were not yet thorough and there were no representatives to contact with retailers to distribute products. Opportunity was that there were many tourists and the government campaigns to support products from local wisdom. Threat was there were many retail stores so that it was very competitive. Development guidelines should include more distribution channels for retailers to cover more areas in Chachoengsao province